High-water-resistance water-based ink and preparation process thereof

By using regenerated cellulose embedded with zirconia particles as water-resistant additives in water-based inks, the problem of poor water resistance of water-based inks is solved, and better water resistance and layering resistance are achieved, meeting the requirements of environmental protection and sustainable development.

CN119684844AActive Publication Date: 2025-03-25HANGZHOU LINAN SHENGHENG DECORATION MATERIALS CO LTD

Patent Information

Application Number
CN202411849405.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

Water-based inks have poor water resistance and are difficult to meet the requirements of environmental protection and sustainable development.

Method used

Regenerated cellulose embedded with zirconia particles is used as a water-resistant additive to form a hydrogen bond network and physically integrate with acrylic emulsion and titanium dioxide to improve the water resistance of the paint film.

Benefits of technology

It significantly improves the water resistance of water-based inks, enhances the water resistance and layering properties of the paint film, and meets the requirements of environmental protection and sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684844A_ABST
    Figure CN119684844A_ABST
Patent Text Reader

Abstract

The invention relates to water-based ink with high water resistance and a preparation process of the water-based ink, and the water-based ink comprises the following raw materials in parts by mass: 100-140 parts of acrylic emulsion; 120 to 160 parts of titanium dioxide; 5 to 15 parts of a thickening agent; 0-5 parts of a functional auxiliary agent; 80 to 100 parts of an organic pigment; 10-20 parts of a pigment dispersant; 20 to 60 parts of ethylene glycol; 400 to 600 parts of deionized water; the adding mass of the water-resistant additive is 0.1-0.2 time of the sum of the mass of the acrylic emulsion and the mass of the titanium dioxide; the water-resistant additive is regenerated cellulose embedded with zirconium oxide particles, the regenerated cellulose is of a microporous structure, the zirconium oxide particles are embedded in the microporous structure of the regenerated cellulose, and the mass ratio of the zirconium oxide particles to the regenerated cellulose is 1: (10-20). The water-based ink provided by the invention has good water resistance and sedimentation resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of water-based inks, and in particular to a highly water-resistant water-based ink and a preparation process thereof. Background Art

[0002] With the continuous advancement of printing technology and the enhancement of environmental awareness, traditional solvent-based inks have gradually failed to meet the requirements of modern society for environmental protection and sustainable development due to their large amount of volatile organic compounds (VOCs), which pose a potential threat to the environment and human health. Therefore, the development of environmentally friendly inks has become an important development direction for the printing industry.

[0003] Water-based inks, because they do not contain volatile organic solvents, greatly reduce VOCs emissions, thereby reducing air pollution, improving the environment for printing operators, and benefiting the health of workers. It can completely eliminate certain toxic and harmful substances in solvent-based inks, eliminate harm to the human body and pollution to packaged goods, improve the overall environmental quality, and is particularly suitable for packaging and printing products with strict hygienic requirements such as tobacco, alcohol, food, beverages, medicines, and children's toys. In addition, it can not only reduce the risk and hidden dangers of fire caused by static electricity and flammable solvents, but also reduce the toxicity of the printed surface and facilitate the cleaning of printing equipment.

[0004] As an environmentally friendly ink, water-based ink has gradually attracted market attention for its advantages such as low VOCs emission, good printing adaptability and color reproducibility. Water-based ink is mainly composed of water-soluble resin, pigment, water, additives, etc. In the printing process, water is used as a solvent or diluent, which effectively reduces pollution to the environment.

[0005] However, there are still some technical challenges in the practical application of water-based inks. For example, since water-based inks often use water or aqueous solutions of small molecule alcohols as solvents or dispersion media, although the water resistance is significantly improved after appropriate modification, its water resistance is still significantly worse than that of solvent-based inks. How to obtain a water-based ink with high water resistance is a technical problem that needs to be solved urgently but is difficult to solve. Summary of the invention

[0006] In order to improve the defect of poor water resistance of water-based ink currently on the market, the present application provides a highly water-resistant water-based ink and a preparation process thereof.

[0007] In the first aspect, the present application provides a highly water-resistant aqueous ink, which adopts the following technical solution: A highly water-resistant water-based ink comprising at least the following raw materials in parts by weight: Acrylic emulsion 100-140 parts; 120-160 parts of titanium dioxide; Thickener 5-15 parts; Functional additives 0-5 parts; 80-100 parts of organic pigment; Pigment dispersant 10-20 parts; 20-60 parts of ethylene glycol; 400-600 parts of deionized water; The ink also contains a water-resistant additive, which is regenerated cellulose embedded with zirconium oxide particles. The regenerated cellulose has a microporous structure, and the zirconium oxide particles are embedded in the microporous structure of the regenerated cellulose. The mass ratio of the zirconium oxide particles to the regenerated cellulose is 1:10-20, and the added mass of the water-resistant additive is 0.1-0.2 times the sum of the mass of the acrylic emulsion and the titanium dioxide.

[0008] By adopting the above technical solution, a water-resistant additive is added in this application, and the water-resistant additive is a special regenerated cellulose material embedded with zirconium oxide particles (it should be noted that it is not a cellulose derivative such as CMC, but regenerated cellulose). Cellulose has very good hydrophilicity due to its large number of hydroxyl groups. Therefore, it is generally believed that adding cellulose to the ink should lead to an increase in the hydrophilicity of the ink, which will naturally lead to a decrease in its water resistance. Therefore, if the water resistance of the paint film is to be improved, adding cellulose is often not a solution of choice.

[0009] However, the inventors of the present application unexpectedly discovered that when the added cellulose has a microporous structure and zirconium oxide particles are embedded in the microporous structure, and its added amount is controlled to be no more than 0.2 times and no less than 0.1 times the sum of the mass of the acrylic emulsion and the titanium dioxide, the addition of hydrophilic cellulose can actually make the paint film have better water resistance.

[0010] This may be because the large number of hydroxyl groups on the surface of regenerated cellulose do give it good hydrophilicity, which allows it to be well and evenly dispersed. The evenly dispersed regenerated cellulose can produce a large number of hydrogen bonds with the water-based resin (acrylic emulsion) and titanium dioxide filler in the ink, and the addition amount is not less than 0.1 times, which means that the large amount of hydrogen bonds introduced can form a relatively complete hydrogen bond network, thereby improving the water resistance of the paint film. In addition, compared with natural cellulose in nature, a large number of microporous structures will be introduced during the phase separation and regeneration process of regenerated cellulose, and these microporous structures will produce obvious capillary phenomena. Therefore, the final paint film will have a large amount of water-based resin and other components embedded in the microporous structure of regenerated cellulose, forming a physical mosaic in addition to the hydrogen bond network, which greatly improves the compatibility and tightness of the materials in the paint film, thereby obtaining better water resistance.

[0011] Of course, the amount of regenerated cellulose added should not be higher than 0.2 times, so as to avoid excessive introduction of hydroxyl groups which significantly increase the hydrophilicity of the paint film, thereby causing a predictable decrease in the water resistance of the paint film. In addition, the microporous structure of regenerated cellulose not only produces capillary adsorption of materials in the paint film, but also causes capillary water absorption. Therefore, if the regenerated cellulose is too large, in addition to the excessive introduction of hydroxyl groups, the capillary water absorption caused by the excessive microporous structure will also cause a decrease in the water resistance of the paint film.

[0012] On the basis of the above, the zirconium oxide embedded in the microporous structure of the regenerated cellulose cooperates with the regenerated cellulose to make the paint film have better water resistance.

[0013] This may be because, on the one hand, as mentioned above, regenerated cellulose shows significantly stronger capillary water absorption than natural cellulose, and zirconium oxide filled in the microporous structure can alleviate this phenomenon to a certain extent; on the other hand, cellulose is soft in texture, and embedded zirconium oxide particles can significantly increase the strength of cellulose, so that the cellulose dispersed in the paint film plays a good pinning role. Overall, embedded zirconium oxide particles can reduce capillary water absorption, and more show the positive effect of cellulose itself forming hydrogen bonds on water resistance.

[0014] Of course, zirconium oxide should not be added excessively (for example, the ratio of zirconium oxide to cellulose should be less than or equal to 1:10). On the one hand, zirconium oxide itself has good hydrophilicity and can also form hydrogen bonds with the hydroxyl groups on the regenerated cellulose, which leads to a decrease in the free hydroxyl groups that can form a hydrogen bond network in the paint film. Whether it is the decrease in the integrity of the hydrogen bond network or the high hydrophilicity caused by zirconium oxide itself, the water resistance of the paint film will decrease. In addition, excessive zirconium oxide will cause excessive blockage of the microporous structure of cellulose, and it will be difficult for materials such as acrylic emulsion and titanium dioxide to produce sufficient physical intercalation with the microporous structure on the regenerated cellulose, and the tightness of mutual bonding will decrease, which will lead to a decrease in the strength and water resistance of the paint film.

[0015] It is also worth noting that the production process of water-based inks cannot avoid a certain degree of heating, and acrylic emulsion is an alkali-soluble resin, so the entire system is alkaline and the temperature is relatively high. Under these conditions, regenerated cellulose is prone to uncontrollable degradation, while zirconium oxide has good thermal insulation properties. When coated on the fibers of regenerated cellulose, it can greatly reduce the possibility of degradation of regenerated cellulose during the production of inks, thereby ensuring the formation of a hydrogen bond network and physical interlocking effect. Of course, the good thermal insulation properties of zirconium oxide also mean that if zirconium oxide is added in excess, the thermal conductivity of the water-based ink will be excessively reduced, and the drying of each area will be uneven during drying and curing. If the drying speed is too low, it will easily lead to a decrease in the adhesion of the paint film.

[0016] Optionally, the thickener is a mixture of sodium alginate and sodium carboxymethyl cellulose in a mass ratio of 1-2:1.

[0017] By adopting the above technical scheme, sodium alginate and sodium carboxymethyl cellulose are both common thickeners for water-based inks, and the combination of the two can play a good thickening and stabilizing role. Among them, sodium carboxymethyl cellulose is a natural polymer compound soluble in water with good thickening properties. Sodium alginate is a polysaccharide extracted from brown algae seaweed, which has excellent gelling ability and stability. By combining these two functional substances, the comprehensive performance of sodium carboxymethyl cellulose plus sodium alginate has been further improved. Stability is also one of the key properties of many products. Sodium carboxymethyl cellulose plus sodium alginate can effectively prevent the sedimentation and aggregation of solid particles or bubbles in liquid and gel systems. Its excellent stability enables the product to remain stable for a long time during storage, transportation and use, and is not easy to stratify and precipitate. This is very important for water-based ink systems with titanium dioxide inorganic particles added.

[0018] It is worth noting that when sodium alginate is present in the thickener, whether the regenerated cellulose in the water-resistant additive is embedded with zirconium oxide particles unexpectedly has a significant effect on the anti-settling and anti-stratification properties of the water-based ink.

[0019] Specifically, the inventors of the present application found in a control experiment that if there is only regenerated cellulose but no zirconium oxide in the water-resistant additive, the anti-stratification performance of the water-based ink will be significantly reduced, which is very unexpected. It is generally believed that zirconium oxide embedded in cellulose will not affect the anti-stratification performance of the water-based ink. This may be because, although sodium alginate can be used to adjust the viscosity of the system, the molecular chain of sodium alginate is unstable and is prone to degradation during the production process at a slightly higher temperature or during high-temperature storage, which leads to unexpected changes in the viscosity of the water-based ink and a decrease in the anti-stratification performance of the water-based ink. Zirconium oxide embedded in regenerated cellulose has a good heat-insulating effect, which can not only avoid high-temperature alkaline hydrolysis of regenerated cellulose, but also significantly reduce the degradation process of sodium alginate, thereby alleviating this problem.

[0020] Optionally, the pigment dispersant is at least one of sodium dodecylbenzene sulfonate, polyethylene glycol diglycidyl ether, tetradecylpyridinium bromide, and cardanol.

[0021] Optionally, the pigment dispersant is a mixture of cardanol and polyethylene glycol diglycidyl ether in a mass ratio of 1:2-3.

[0022] By adopting the above technical solution, cardanol is a green industrial raw material extracted and refined from natural cashew nut shell oil, which has a wide range of applications. As a surfactant, cardanol can significantly improve the dispersion performance of pigments in water-based inks. Therefore, cardanol has good dispersibility and stability in coatings and inks, and can improve the color and durability of paint films.

[0023] Polyethylene glycol diglycidyl ether is a polymer compound obtained by the reaction of ethylene glycol and glycidyl ether. It has the main characteristics of high water solubility, surfactant properties, ionic properties, biocompatibility and chemical modifier properties. It is widely used in surfactant applications in water-based systems. It can also improve the dispersibility and stability of pigments, thereby improving the color and durability of the paint film.

[0024] And the inventors of the present application found that, compared with the use of cardanol or polyethylene glycol diglycidyl ether alone, the use of the two in combination did not significantly change the dispersibility, but it did make the paint film have better water resistance. This may be because, as mentioned above, polyethylene glycol diglycidyl ether not only has surfactant properties, but also has chemical modifier properties, which may play the role of a cross-linking agent, and the two side end epoxy groups are respectively opened and react with the phenolic hydroxyl groups on cardanol, the alcoholic hydroxyl groups on the regenerated cellulose, and the active groups on the water-based resin, thereby forming a morphology similar to a three-dimensional cross-linked network, so that the paint film has better water resistance.

[0025] Optionally, the water-resistant additive is prepared by the following process: A1. Dispersing zirconium oxide: placing zirconium oxide in a solvent and dispersing it ultrasonically to obtain a dispersion, wherein the solvent is at least one of acetone, dioxane, dimethylacetamide, and N-methylpyrrolidone; A2, dissolving, adding cellulose diacetate into the dispersion and dissolving to obtain a blended liquid, wherein the added concentration of cellulose diacetate is 8-12wt%; and the added mass ratio of the zirconium oxide to the cellulose diacetate is 1:10-20; A3, phase separation solidification, placing the blended liquid in a phase separation bath, making the cellulose diacetate phase separate into a microporous structure and making the zirconium oxide adhere to the fiber structure, filtering out to obtain a semi-finished product, wherein the phase separation bath is an aqueous solution of a small molecule alcohol, the surface tension of the phase separation bath is not more than 40mN / m, and the small molecule alcohol is at least one of ethanol, propanol, and isopropanol; A4. Hydrolysis regeneration: the semi-finished product is mixed with a sodium hydroxide solution to hydrolyze the cellulose diacetate to remove the acetate group and regenerate the cellulose, which is filtered out and washed to obtain the regenerated cellulose embedded with zirconium oxide particles.

[0026] By adopting the above technical solution, in step A3, the phase separation bath with low surface tension can improve its penetration ability, so as to more quickly exchange with the solvent in the blend liquid to form micropores with smaller pore sizes, and the lower concentration of cellulose diacetate makes the pores smaller but more numerous. Therefore, the phase separation bath with low surface tension can make the final regenerated cellulose have a large number of small-sized microporous structures, so that after adding water-based ink, a better physical mosaic effect can be formed, and it is easier to form a hydrogen bond network through more evenly dispersed and exposed hydroxyl groups, thereby improving water resistance and anti-stratification performance.

[0027] Optionally, in step A3, the blended liquid is injected into the stirring phase separation bath by spraying, the spraying speed of the blended liquid is 2-10 L / min, and the stirring speed of the phase separation bath is 50-100 r / min.

[0028] By adopting the above technical solution and the special spray phase separation method, although the blended liquid can be injected into the phase separation bath in a continuous manner, during the phase separation process, cellulose diacetate is not easy to form a continuous structure such as a film, strip, or sheet that is interconnected, but is more likely to form independent irregular particles, which greatly reduces the contact area between the final regenerated cellulose and each material, thereby forming a larger amount of hydrogen bonds to obtain good anti-stratification performance and water resistance.

[0029] Optionally, the step A4 specifically includes the following steps: A41, cold mixing, blending the semi-finished product with the sodium hydroxide solution, and controlling the system temperature to be no greater than 20° C. to obtain a cold mixing system; A42, heating and hydrolysis, heating the cold mixed system to 60-80°C to hydrolyze the cellulose diacetate under alkaline conditions to regenerate the cellulose; A43, filtering and washing, filtering and washing the regenerated cellulose in the hydrolysis system and the zirconium oxide embedded in the micropores of the regenerated cellulose until they are neutral, thus obtaining a water-resistant additive.

[0030] By adopting the above technical solution, compared with directly mixing the semi-finished product with sodium hydroxide solution under high temperature conditions for hydrolysis and regeneration, the method of cold mixing first and then heating for hydrolysis is adopted, which can ensure that the sodium hydroxide is first evenly attached to the fiber and then hydrolyzed, thereby improving the hydrolysis uniformity of cellulose diacetate, and accordingly, can improve the defect resistance of water-based ink.

[0031] Optionally, the concentration of the sodium hydroxide solution is 0.2-1 g / L, and the ratio of the mass of sodium hydroxide in the sodium hydroxide solution to the mass of cellulose diacetate added in step A2 is 1:2-3.

[0032] By adopting the above technical scheme, by controlling the amount of sodium hydroxide added during blending, and combining a special process of cold mixing first and then heating and hydrolyzing, in the cold mixing stage, sodium hydroxide first adheres to the surface of cellulose diacetate more evenly, and in the heating and hydrolysis stage, the surface of cellulose diacetate is hydrolyzed into regenerated cellulose, while the interior is still cellulose diacetate due to insufficient sodium hydroxide. This treatment makes the final water-resistant additive have a special skin-core structure, in which the surface is fully hydrolyzed regenerated cellulose, and the inner core is incompletely hydrolyzed cellulose diacetate; the introduction of regenerated cellulose with a large number of hydroxyl groups on the surface can ensure that the water-resistant additive forms a hydrogen bond network with the rest of the materials, while the cellulose diacetate in the inner core has higher mechanical strength, and with the embedded zirconium oxide, the water-resistant additive has higher strength, is not easy to be over-broken during the preparation of water-based ink, and better plays the role of improving water resistance and pinning to improve strength.

[0033] In a second aspect, the present application provides a process for preparing a water-based ink, which adopts the following technical solution: A preparation process of water-based ink, the following process steps: S1, stirring and preliminarily mixing, blending and uniformly mixing all raw materials except acrylic emulsion and water-resistant additive, and then adding acrylic emulsion and stirring uniformly to obtain a preliminarily mixed material; S2, sand milling, transferring the primary mixed material to a sand mill for a first-stage sand milling, then adding a water-resistant additive for a second-stage sand milling, and filtering the material after the sand milling is completed; S3. Packaging, storage and transportation.

[0034] Optionally, in step S2, during the first stage of grinding, cooling water is used for indirect cooling to control the grinding temperature to 25-35°C, and the first stage of grinding is completed when the fineness is not greater than 15 μm; then the cooling water is cut off and a water-resistant additive is added, and the grinding state is maintained until the temperature in the grinder reaches 50-60°C, completing the second stage of grinding.

[0035] By adopting the above technical scheme, a special two-stage grinding method can ensure a good grinding effect by first performing a high-viscosity grinding at a low temperature, and further adding a water-resistant additive and grinding at a low viscosity at a high temperature. On the one hand, it can avoid the problems of difficulty in discharging and clogging of the sand mill caused by high viscosity, and on the other hand, it can avoid the softer regenerated cellulose from being excessively sanded and crushed, making it difficult to play the role of local pinning and physical interlocking. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a SEM picture of a typical water-resistant additive prepared in this application. DETAILED DESCRIPTION

[0037] The present application is described in further detail below.

[0038] The following is an example of the preparation of the water-resistant additive disclosed in this application: Preparation Example 1 The water-resistant additive in this preparation example is prepared by the following process steps: A1. Dispersing zirconium oxide: placing zirconium oxide in a solvent and ultrasonically dispersing it to obtain a dispersion. The solvent is N-methylpyrrolidone. The concentration of zirconium oxide added is controlled to be 0.67wt%. The ultrasonic dispersion process only needs to ensure that the zirconium oxide is fully dispersed, and conventional adjustments can be made. In this preparation example, the ultrasonic power is 50W, the ultrasonic time is 15min, and the zirconium oxide is purchased from DKK Company (Daiichi Rare Element Chemical Industry Co., Ltd.) of Japan. The specific model is UEP-50. 50 The surface area is 0.07-0.27 μm and the specific surface area is 40-60 m 2 / g.

[0039] A2. Dissolving: adding cellulose diacetate into the dispersion and dissolving to obtain a blended liquid, wherein the added concentration of cellulose diacetate is 10wt%; in the blended liquid, the added mass ratio of zirconium oxide to cellulose diacetate is 1:14.9; cellulose diacetate is purchased from Daicel Corporation, and the specific model is CAFBLO® Flake L-50, and its esterification rate (acetic acid binding rate) is 54%-56%.

[0040] A3, phase separation solidification, injecting the blended liquid into the stirring phase separation bath by spraying through a nozzle, so that the diacetate cellulose is phase-separated into a microporous structure and the zirconium oxide is attached to the fiber structure, and the semi-finished product is obtained by filtering, and the phase separation bath is an aqueous solution of small molecule alcohol. In this preparation example, the phase separation bath is an aqueous solution of ethanol, and the surface tension of the phase separation bath is about 35mN / m by controlling the concentration of ethanol; the injection speed of the blended liquid is 6L / min, and the stirring speed of the phase separation bath is 75r / min.

[0041] A4, hydrolysis regeneration, the semi-finished product is mixed with sodium hydroxide solution to hydrolyze the cellulose diacetate to remove the acetate group and regenerate cellulose, and the regenerated cellulose embedded with zirconium oxide particles is obtained by filtering and washing; specifically, this step adopts a process of cold mixing first and then hot hydrolysis, and the specific steps are as follows: A41. Cold mixing: blending the semi-finished product with the sodium hydroxide solution, and controlling the system temperature to be no greater than 20°C. Specifically, in this preparation example, the system temperature is controlled to be 15°C to obtain a cold mixing system. The concentration of the sodium hydroxide solution is controlled to be 0.5 g / L. In step A2 of this preparation example, a total of 50 g of cellulose diacetate is used. Therefore, in this step, the total amount of sodium hydroxide added needs to be controlled to be 20 g. Since the concentration of the sodium hydroxide solution is controlled to be 0.5 g / L, a total of 40 L of sodium hydroxide solution is required to ensure that the ratio of the mass of sodium hydroxide in the sodium hydroxide solution to the mass of cellulose diacetate added in step A2 is 1:2.5.

[0042] A42, heating and hydrolysis, heating the cold mixed system to 70°C to hydrolyze the cellulose diacetate under alkaline conditions to regenerate the cellulose into regenerated cellulose; A43, filtering and washing, filtering and washing the regenerated cellulose in the hydrolysis system and the zirconium oxide embedded in the micropores of the regenerated cellulose until neutral, to obtain a water-resistant additive; the scanning electron microscope image of the obtained water-resistant additive is as follows Figure 1 shown.

[0043] Preparation Example 2-7 The main difference between Preparation Example 2-7 and Preparation Example 1 is that each preparation process step is appropriately adjusted, as shown in the following table for details:

[0044] It should be noted that the preparation example 6 of the present application does not adopt the process of cold mixing followed by hot hydrolysis, but directly blends the semi-finished product with a sodium hydroxide solution at a temperature of 80° C. In the preparation example 8, no zirconium oxide particles are added, so the water-resistant additive obtained is only cellulose material.

[0045] The following are examples of water-based inks disclosed in this application: Example 1: This application example discloses a highly water-resistant aqueous ink. The highly water-resistant aqueous ink specifically comprises the following raw materials in parts by weight: Acrylic emulsion 120 parts; 140 parts of titanium dioxide; Thickener 10 parts; 3 parts of functional additives; 90 parts of organic pigment; Pigment dispersant 15 parts; 40 parts of ethylene glycol; 500 parts of deionized water; 39 parts of water-resistant additive, which is 0.15 times the sum of the added mass of acrylic emulsion and titanium dioxide.

[0046] Specifically, the acrylic emulsion in this embodiment is purchased from Dow Chemical's RESIN HF-05A water-based self-crosslinking thermosetting acrylic resin, and its solid content is about 40%; the titanium dioxide is specifically Bluestar Dahua's anatase titanium dioxide DHA-100, and the thickener is a mixture of sodium alginate and sodium carboxymethyl cellulose in a mass ratio of 1.5:1; the functional additive is specifically 1 part of defoaming agent to 2 parts of leveling agent, the defoaming agent is specifically Dow Chemical's DC65 silicone defoaming agent, and the leveling agent is specifically BYK-333 silicone leveling agent; the organic pigment can be conventionally selected, and in this embodiment, the organic pigment is phthalocyanine blue BGS; the pigment dispersant is a mixture of cardanol and polyethylene glycol diglycidyl ether in a mass ratio of 1:2.5.

[0047] The highly water-resistant aqueous ink in this embodiment is prepared by the following process steps: S1, stirring and preliminarily mixing, blending and uniformly mixing all raw materials except acrylic emulsion and water-resistant additive, and then adding acrylic emulsion and stirring uniformly to obtain a preliminarily mixed material; S2, sand grinding, transferring the primary mixture to a sand mill for a first-stage sand grinding, then adding a water-resistant additive for a second-stage sand grinding, filtering and discharging the material after the sand grinding is completed; specifically, during the first stage of grinding, indirect cooling is performed by cooling water to control the grinding temperature to 30°C, and the first stage of grinding is completed by grinding to a fineness of no more than 15μm; then the cooling water is cut off and the water-resistant additive is added, and the grinding state is maintained until the temperature in the grinder reaches 55°C, completing the second stage of grinding.

[0048] S3. Packaging, storage and transportation.

[0049] The main difference between Example 2-7 and Example 1 is that the raw material composition and process steps are adjusted, as shown in the table below.

[0050] Specifically, The main difference between Example 2 and Example 1 is that although the addition amount of the thickener is adjusted to 15 parts, it is still a mixture of sodium alginate, sodium alginate and sodium carboxymethyl cellulose in a mass ratio of 1.5:1, the functional additives are specifically 0.5 parts of defoaming agent and 0.5 parts of leveling agent, and although the addition amount of the pigment dispersant is adjusted to 10 parts, it is still a mixture of cardanol and polyethylene glycol diglycidyl ether in a mass ratio of 1:2.5.

[0051] Similar to Example 2, the main difference between Example 3 and Example 1 is that the type and ratio of thickener, the type and ratio of functional additives, and the type and ratio of pigment dispersants are not changed, and only the addition amount is adjusted.

[0052] The main difference between Example 4 and Example 1 is that, although the added amount of the thickener is still 10 parts, the thickener is only sodium alginate, and CMC-Na is not added.

[0053] The main difference between Example 5 and Example 6 and Example 1 is that, although the added amount of the pigment dispersant is still 15 parts, the pigment dispersant in Example 5 is only polyethylene glycol diglycidyl ether, and the pigment dispersant in Example 6 is only cardanol.

[0054] The main difference between Example 7 and Example 1 is that, although the added amount of the pigment dispersant is still 15 parts, the pigment dispersant in Example 7 is only sodium dodecylbenzene sulfonate, and the added water-resistant additive is prepared in Preparation Example 2.

[0055] The main difference between Example 8 to Example 12 and Example 1 is that the water-resistant additive added in Example 8 is prepared in Preparation Example 3, the water-resistant additive added in Example 9 is prepared in Preparation Example 4, the water-resistant additive added in Example 10 is prepared in Preparation Example 5, the water-resistant additive added in Example 11 is prepared in Preparation Example 6, and the water-resistant additive added in Example 12 is prepared in Preparation Example 7.

[0056] Comparative Example Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that the water-resistant additive used in Comparative Example 1 is not the water-resistant additive prepared in each preparation example of the present application, but conventional commercially available microcrystalline cellulose, specifically Toncellus® TC105 of Dongchen Pharmaceutical, whose D 50 The thickness is 20 μm and the bulk density is about 0.25 g / cm 3 .

[0057] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that the water-resistant additive added in Comparative Example 2 is prepared in Preparation Example 8.

[0058] Comparative Example 3 The only difference between Comparative Example 3 and Example 1 is that excessive water-resistant additive is added in Comparative Example 3, and the added amount is 78 parts, which is 0.3 times the sum of the added masses of acrylic emulsion and titanium dioxide.

[0059] Comparative Example 4 Comparative Example 4 The only difference between Comparative Example 3 and Example 1 is that in Comparative Example 4, sufficient water-resistant additive is not added, and the added amount is 78 parts, which is 0.3 times the sum of the added mass of acrylic emulsion and titanium dioxide;

[0060] Performance testing and data Water resistance, alcohol resistance The water resistance of the water-based ink prepared in each embodiment and comparative example of the present application is carried out according to the water resistance and alcohol resistance test of standard QB568-1983. Specifically, according to QB568, 10 qualitative filter papers soaked with aqueous solution or anhydrous ethanol are covered on 1 / 2 part of the ink paint film, and after adding weights and standing for 24 hours, the grade is evaluated according to the changes in the paint film. According to 5 grades, the higher the grade, the better the water resistance and alcohol resistance. It should be noted that although the scheme has been abolished at present, it is still a good test method for indicating the water resistance and alcohol resistance of the paint film, and its performance detection process is simple, and the result is intuitive and observable.

[0061] Anti-settling performance The water-based ink prepared in each embodiment and comparative example was placed in a transparent sealed container, centrifuged at 200 rpm for 12 hours in a low-speed centrifuge, and then placed in an oven at 60°C for 7 days. After being taken out, it was observed whether there was stratification. The flocculation and sedimentation degree at the bottom were observed and evaluated according to 5 levels. The higher the level, the better the anti-sedimentation performance.

[0062] The performance parameters of the paint films obtained in each embodiment and comparative example are shown in the following table:

[0063] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

Claims

1. A highly water-resistant aqueous ink, characterized in that: At least the following raw materials by weight: Acrylic emulsion 100-140 parts; 120-160 parts of titanium dioxide; Thickener 5-15 parts; Functional additives 0-5 parts; 80-100 parts of organic pigment; Pigment dispersant 10-20 parts; 20-60 parts of ethylene glycol; 400-600 parts of deionized water; The ink also contains a water-resistant additive, which is regenerated cellulose embedded with zirconium oxide particles. The regenerated cellulose has a microporous structure, and the zirconium oxide particles are embedded in the microporous structure of the regenerated cellulose. The mass ratio of the zirconium oxide particles to the regenerated cellulose is 1:10-20, and the added mass of the water-resistant additive is 0.1-0.2 times the sum of the mass of the acrylic emulsion and the titanium dioxide.

2. The highly water-resistant aqueous ink according to claim 1, characterized in that: The thickener is a mixture of sodium alginate and sodium carboxymethyl cellulose in a mass ratio of 1-2:

1.

3. The highly water-resistant aqueous ink according to claim 1, characterized in that: The pigment dispersant is at least one of sodium dodecylbenzene sulfonate, polyethylene glycol diglycidyl ether, tetradecylpyridinium bromide and cardanol.

4. The highly water-resistant aqueous ink according to claim 3, characterized in that: The pigment dispersant is a mixture of cardanol and polyethylene glycol diglycidyl ether in a mass ratio of 1:2-3.

5. A highly water-resistant aqueous ink according to any one of claims 1 to 4, characterized in that: The water-resistant additive is prepared by the following process: A1. Dispersing zirconium oxide: placing zirconium oxide in a solvent and dispersing it ultrasonically to obtain a dispersion, wherein the solvent is at least one of acetone, dioxane, dimethylacetamide, and N-methylpyrrolidone; A2, dissolving, adding cellulose diacetate into the dispersion and dissolving to obtain a blended liquid, wherein the added concentration of cellulose diacetate is 8-12wt%; and the added mass ratio of the zirconium oxide to the cellulose diacetate is 1:10-20; A3, phase separation solidification, placing the blended liquid in a phase separation bath, making the cellulose diacetate phase separate into a microporous structure and making the zirconium oxide adhere to the fiber structure, filtering out to obtain a semi-finished product, wherein the phase separation bath is an aqueous solution of a small molecule alcohol, the surface tension of the phase separation bath is not more than 40mN / m, and the small molecule alcohol is at least one of ethanol, propanol, and isopropanol; A4. Hydrolysis regeneration: the semi-finished product is mixed with a sodium hydroxide solution to hydrolyze the cellulose diacetate to remove the acetate group and regenerate the cellulose, which is filtered out and washed to obtain the regenerated cellulose embedded with zirconium oxide particles.

6. The highly water-resistant aqueous ink according to claim 5, characterized in that: In the step A3, the blended liquid is injected into the stirring phase separation bath by spraying, the spraying speed of the blended liquid is 2-10 L / min, and the stirring speed of the phase separation bath is 50-100 r / min.

7. The highly water-resistant aqueous ink according to claim 5, characterized in that: The step A4 specifically includes the following steps: A41, cold mixing, blending the semi-finished product with the sodium hydroxide solution, and controlling the system temperature to be no greater than 20° C. to obtain a cold mixing system; A42, heating and hydrolysis, heating the cold mixed system to 60-80°C to hydrolyze the cellulose diacetate under alkaline conditions to regenerate the cellulose; A43, filtering and washing, filtering and washing the regenerated cellulose in the hydrolysis system and the zirconium oxide embedded in the micropores of the regenerated cellulose until they are neutral, thus obtaining a water-resistant additive.

8. The highly water-resistant aqueous ink according to claim 1, characterized in that: The concentration of the sodium hydroxide solution is 0.2-1 g / L, and the ratio of the mass of sodium hydroxide in the sodium hydroxide solution to the mass of cellulose diacetate added in step A2 is 1:2-3.

9. The production process of the water-based ink according to any one of claims 1 to 8, characterized in that: The process steps include: S1, stirring and pre-mixing, blending and mixing all raw materials except acrylic emulsion and water-resistant additives, and then adding acrylic emulsion and stirring to obtain a pre-mixed material; S2, sand milling, transferring the primary mixed material to a sand mill for a first-stage sand milling, then adding a water-resistant additive for a second-stage sand milling, and filtering the material after the sand milling is completed; S3. Packaging, storage and transportation.

10. The highly water-resistant aqueous ink according to claim 9, characterized in that: In step S2, during the first grinding, the grinding temperature is controlled to 25-35° C. by indirect cooling with cooling water, and the first grinding is completed when the fineness is not greater than 15 μm; Then cut off the cooling water and add water-resistant additives, keep grinding until the temperature in the grinder reaches 50-60°C, and complete the second stage grinding.

Citation Information

Patent Citations

  • Non-woven microfiber print receptive surface

    CN112261926A

  • Pigment disperser, pigment dispersing body, writing and recording pigment ink

    CN1260365A

  • Water-soluble azo compound and salt thereof, ink composition and colored body

    JP2016204446A

  • Polyuronic acid derivative and aqueous ink composition comprising polyuronic acid derivative

    WO2004011502A1

  • Ink-accepting layer forming material and aqueous ink

    WO2005000594A1

Cited By

  • Light-resistant water-based titanium dioxide ink and preparation method thereof

    CN120966310A